Determinants of Commuter Worker Income in South Sulawesi during the Covid-19 Pandemic - Nur Hilda Triany (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2021)
The development and ease of access to transportation in South Sulawesi Province opens up opportunities for the workforce to work in areas that are administratively different from their residence as commuters. Commuter workers tend to increase every year. When Covid-19 hit the economy in Indonesia, te government issued various policies to suppress the spread of the Covid-19 virus. One of them is by implementing Large-Scale Social Restrictions (PSBB) which was also adapted by the South Sulawesi Provincial Government. The impact of the Covid-19 pandemic on commuter workers is still not a concern, especially even though the restrictions on economic and social activities have a significant impact on the working hours and income of commuter workers. This study determines the factors that affect the income of commuter workers during the Covid-19 pandemic. Based on the results of the August 2020 National Labor Force Survey (Sakernas) data processing, it shows that the income received by commuter workers during the Covid-19 pandemic is influenced by the variables of working hours, business fields, employment status, policies for implementing Work from Home, education level and gender.